The frequency of the secondary vegetation period in collective types of soy - Білявська, Л. Г.; Рибальченко, А. М. (Scientific Progress & Innovations, 2018)
The results of studying the duration of the vegetation period of 145 collections of soybeans during 2013–2015 are presented. Based on statistical analysis of the data, the coefficient of variation (V) of the vegetation period according to the collection samples was less than 10 % and varied from 0.5 % in the sample ARSRIHFF-76 (All-Russian Scientific Research Institute of Hunting and Fur Farming) to 4 % of Merlin sample. Regression coefficient (bi), characterizing the degree of ecological plasticity in the collection of samples ranged from -3.31 to 3.23 to Merlin grade class at El Dorado. In each group of ripeness samples were selected which proved to be stable. According to the environmental assessment for the regression coefficient (degree of plasticity) and sustainability set the relative value of 28 genotypes, which were stable (bi from 0 to 1) for the duration of the growing season. 6 samples was in ultra precocious group, 17 samples was in precocious group and 5 samples was in late ripening group. The samples Zlata, Biliavka, Lada, Dione, Anastasia, OAC Vision was stable (bi from 0 to 1) in ultra precocious group. The regression coefficient ranged from 0.08 (Zlata) to the 0.61 (OAC Vision and Anastasia). Other samples responded more to changes in growing conditions. The coefficient of variation in the samples in this maturity group varied from 0.62 % to 2.69 %. 17 stable genotypes selected in the most numerous precocious group: Precarpathian 96, Silver Ruth, Roxolana, Denis, Princess, ARSRIHFF-76, Larisa, Podiaka, Adamos, Ustia, Anzhelika, Suziria, Krasa Podillia, Osoblyva, Deimos, Sylvia. The regression coefficient ranged from 0.02 (Precarpathian 96) to 0.96 (Nattawa). The coefficient of variation in the samples in this maturity group ranged from 0.5 % to 4 %. In the middle-ripening group (121–140 days), the regression coefficient (bi) in the samples was 1>bi. Galyna and Don’ka maximum approaching maturity in the group to environmentally plastic with a regression coefficient 1.38 in both varieties. In late ripening, genotypes such as Del'ta, Vilana, Sedmytsia, Black Jack 21, Hejiao 87-94-3 have been identified. The regression coefficient was 0.36 in the Delta variety to 0.89 in the Hejiao 87-94-3 sample. The coefficient of variation (V) length of the growing season in late group of samples ranged from 0.7 % to 2.45 %. Selected genotypes are promising for breeding and practical use.